Non-verbal Skills: Unavoidable in Communication - Lamichhane, Yog Raj (REPOSITIONING The Journal of Business and Hospitality, 2016)
This paper aims to define communication and incorporate differences between verbal and non-verbal communication. The special focus is given to different kinds of non-verbal skills with their color and creed. Their contribution in professional field is critically examined. As communication is an ongoing and complex process of transmission and reception of message, the implication of non-verbal communication is indispensable. When verbal and non-verbal cues are in conflict, verbal skills are virtually disregarded and the meaning and implication of ‘what’ heavily depends on non-verbal signs and symbols. The paper also highlights the different forms of vocalic and non-vocalic nonverbal cues with rational categorization. It also explores space in which culture and gender affect non-verbal communication by creating different meanings of particular item of behaviors. In this way, this paper attempts to excavate the importance of non-verbal communication in professional life. Repositioning Vol.1(1) 2016: 91-98